FACTORS THAT DETERMINE THE USE OF TAUTOLOGIES AND PLEONASMS IN SPEECH COMMUNICATION (Western European Journal of Linguistics and Education, 2024)
This article describes the theoretical foundations of the study of tautologies and pleonasms in linguistics. The studied linguistic phenomena and their features are considered. The distinctions between the concepts of "tautology" and "pleonasm" are defined. The methods of studying tautology and pleonasm in linguistics are presented. The author identifies the factors that determine the use of tautologies and pleonasms in speech communication.